A novel hydrophobin encoded by hgfII from Grifola frondosa exhibiting excellent self-assembly ability - Yang, Jiuxia; Ge, Lu; Song, Bo; Ma, Zhongqiang; Yang, Xiaotian; Wang, Bo; Dai, Yixin; Xu, Haijin; Qiao, Mingqiang (Frontiers in Microbiology, 2022)
Hydrophobins are small proteins from filamentous fungi, which have remarkable self-assembly properties of great potential, e.g., as drug carriers and as anti-bacterial agents, but different hydrophobins, with improved properties, are needed. HGFI (a hydrophobin from Grifola frondosa) is a class I hydrophobin, which can self-assemble into rodlet structures with a length range 100-150 nm. In this study, we identified a new hydrophobin gene (hgfII) from the mycelium of Grifola frondosa with a much higher transcriptional level than hgfI. Heterologous expression of hgfII was accomplished in the Pichia pastoris. X-ray photoelectron spectroscopy and water contact angle assay measurements revealed that HGFII can self-assemble into a protein film at the air-solid interface, with circular dichroism and thioflavin T fluorescence studies showing that this effect was accompanied by a decrease in α-helix content and an increase in β-sheet content. Using atomic force microscopy, it was shown that HGFII self-assembled into rodlet-like structures with a diameter of 15-30 nm, showing that it was a class I hydrophobin, with self-assembly behavior different from HGFI. The surface hydrophobicity of HGFII was stronger than that of HGFI, meanwhile, in emulsification trials, HGFII displayed better dispersive capacity to the soybean oil than HGFI, producing a more stable and durable emulsion.